Exergy and economic investigation of different strategies of hybrid systems consisting of gas turbine (GT) and solid oxide fuel cell (SOFC) - Maroufi, Arman; Pirkandi, Jamasb; Ommian, Mohammad (International Journal of Integrated Engineering, 2022)
Gas turbines and solid oxide fuel cells can be combined in two different strategies to create a new high-efficiency hybrid system. In most hybrid systems, the fuel cell is located directly before the combustion chamber (pressurized type) or after the turbine (atmospheric type). The indirect hybrid system is another compound that has been less studied. In this system, the fuel cell and the gas turbine cycle are located in two separate cycles and heat exchange was done by a heat exchanger. The main purpose of this article is to compare the exergy and economic performance of direct and indirect hybrid systems. The results show that the direct hybrid system with pressurized fuel cell has better performance than the other two types of hybrid system. High electrical efficiency, low rate of irreversibility and pollution, and low cost of electricity generation, as well as appropriate cost of purchase, installation and system setup, are the characteristics of this type of hybrid systems. Analyzes of this study showed that the only positive feature of direct atmospheric fuel cell systems is high production capacity and indirect hybrid systems are less efficient than direct systems.